Implementation of Sustainable Tourism Development Policies in Bandung - Sundawa Bachtiar (Universitas Sultan Ageng Tirtayasa, 2022)
Tourism policy is created to provide tourists and the community with certainty about tourism development, maximizing benefits for stakeholders while minimizing negative effects, costs, and other impacts. Bandung relies on tourism for local revenue, so the city government must consider a tourism development concept that preserves natural, social, and cultural resources for future generations. Sustainable tourism is developing quickly and favorably for the local population and the environment. This research discusses the implementation of sustainable tourism policies in Bandung. This study used qualitative research to describe and analyze social phenomena, events, and activities and to obtain current information. According to the study, sustainable tourism development in Bandung is a policy in development with economic, socio-cultural, and environmental dimensions built on a foundation of justice for current and future generations, requiring policy synergy with a multi-sectoral and multidisciplinary approach. Participation, local ownership, resource sustainability, community goals, carrying capacity, monitoring/evaluation, accountability, training, and promotion.